Current design (onlay) PFA implants have similar complication and reoperation rates compared to those of TKA for isolated PF osteoarthritis: a systematic review with quantitative analysis. Issue 5 (11th August 2016) - Vasta, Sebastiano; Papalia, Rocco; Zampogna, Biagio; Espregueira-Mendes, João; Amendola, Annunziato
Abstract : Importance: Patellofemoral osteoarthritis (PFOA) is a common problem in the active population, affecting 2–11% of men and 8–24% of women over 55 years of age. Conservative measures are often ineffective, and patellofemoral arthroplasty (PFA) is an appealing solution considering that it is minimally invasive procedure, without burning any bridges if conversion to a total knee arthroplasty (TKA) is required. Objective: This work aims to systematically review the current available literature on outcomes from PFA or TKA for isolated PFOA. In particular, the research questions are: (1) Is the revision surgery rate higher in PFA than in TKA? (2) Is there any difference in conversion to TKA or reoperation rates between inlay and onlay implant design? (3) What influence has tibiofemoral osteoarthritis (TFOA) progression in PFA complication rate? (4) How many PFAs are revised or converted to TKA because of TFOA progression? Evidence review: A comprehensive search was performed through PubMed, Cochrane Library, Scopus, CINAHL and Google Scholar databases to search for relevant studies on PFA. Inclusion and exclusion criteria were defined. A 20-item methodological quality tool for assessing case series studies was used. Findings: Thirty-seven papers were found to be case series, and one was a case–control study (PFA vs TKA). The general methodology level was weak. However, PFAs have a statistically significant higher complication and consequently reoperation rate, with a statistically significant lower survivorship rate compared to TKA for PFOA. When taking into consideration PFA implant design, those numbers were different. Newer PFA designs, contrary to old ones, showed comparable complication and revision rates to those of TKA. However, newer PFAs' survivorship is still significantly lower than TKAs' one. Although TFOA progression is not necessarily a complication, it represents up to one-third of the reasons for PFA requiring revision, playing a major role in implant's survivorship. Conclusions and relevance: There is a lack of high-level evidence on PFA. However, PFAs with newer implant design showed to be as reliable in terms of the complication and reoperation rate as TKA. Progression of TFOA still remains an issue, representing up to one-third of the overall complications. Level of evidence: III, systematic review of level IV and V studies.